2014
DOI: 10.3892/ol.2014.2406
|View full text |Cite
|
Sign up to set email alerts
|

Transsacral excision with pre-operative imatinib mesylate treatment and approach for gastrointestinal stromal tumors in the rectum: A report of two cases

Abstract: Gastrointestinal stromal tumors (GISTs) are rare in the rectum. Radical surgery, such as an abdominoperineal resection, is necessary for large rectal GISTs, which can result in the loss of function of involved organs. Imatinib mesylate can be used as perioperative therapy and may reduce tumor size, and it is now approved for use in the adjuvant therapy of locally resected anorectal GISTs. The present study describes two cases of large rectal GISTs, for which abdominoperineal resections were initially planned. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Though rectal GISTs are less common than non-rectal GISTs, accounting for ~5% of total GISTs ( 28 ), they remain the focus of studies, as the symptoms for rectal GISTs appear earlier compared with the symptoms of GISTs located in the enterocoelia. Rectal GISTs may also be detected by digital rectal examination, fiber colonoscopy and ultrasonic endoscopy ( 29 ). The principle of surgery for rectal GISTs is different from the principle for rectal cancer, as no lymph node dissection or TME resection is required, but a tumor-free resection margin and complete resection are necessary ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Though rectal GISTs are less common than non-rectal GISTs, accounting for ~5% of total GISTs ( 28 ), they remain the focus of studies, as the symptoms for rectal GISTs appear earlier compared with the symptoms of GISTs located in the enterocoelia. Rectal GISTs may also be detected by digital rectal examination, fiber colonoscopy and ultrasonic endoscopy ( 29 ). The principle of surgery for rectal GISTs is different from the principle for rectal cancer, as no lymph node dissection or TME resection is required, but a tumor-free resection margin and complete resection are necessary ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“… 29 IM is also the only TKI currently available for neoadjuvant therapy (nIM), and the standard dose is 400 mg/day. 30 , 31 However, a case report also showed that sunitinib was selected for neoadjuvant therapy for gastrointestinal stromal tumors firstly. First-line neoadjuvant therapy with sunitinib produced good clinical outcomes in 2 patients with very large rectal GISTs adjacent to the prostate and bladder.…”
Section: Treatment Of Rectal Gistsmentioning
confidence: 99%
“…Imatinib mesylate is a competitive inhibitor for kit, PDGFRA and for tyrosine kinases. And can give 80% to complete pathological response 17 . C-kit shows positivity in cytoplasm and in cell membrane.…”
Section: Introductionmentioning
confidence: 99%